Successful Surgical Treatment of a Rare Case of Acute Isolated Right Ventricle Wall Rupture Caused by Distal Circumflex Coronary Artery Occlusion - Emrah Erdogan; Yakup Kilic; Hasim Tuner; Sahin Sahinalp; Anantharaman Ramasamy (Brazilian Journal of Cardiovascular Surgery, 2021)
Abstract We describe a rare case of isolated right ventricular inferior free-wall rupture and cardiogenic shock caused by occlusion of the distal left circumflex coronary artery. Our case highlights the central role of transthoracic echocardiography in identifying unexpected conditions that can guide management - in our case involving early surgical intervention, thus leading to favourable patient outcomes.